Pertautan Teologi dan Politik: Kajian terhadap Aliran Religio-Politik Syi’ah dan Khawarij - Mustain Mustain (Universitas Islam Negeri Mataram, 2009)
The history of emergence of sects of Islamic theology can not be separated from political issues as shown in the history of Shiite, Khawarij, Murjiah, Jabariyah, Qadariyah, Mu'tazilite, and Ash'arite. This paper tries to assess such linkage, particularly in the case of Shiite and Khawarij. The emergence of both sects was backed by sharp tribal political competition among the supporters of Ali ibn Abi Talib; both sects then showed their characteristics more as political stream (religio-political) rather than sects of theology. Although both, especially Khawarij, have important contributions in the debate concerning major sins commit which then lead to debate about broader and in-depth issues of divinity, but their political activities are more dominant than their theological thoughts. While the Shiite was preoccupied by searching for the ideal figure of priest (imam), Khawarij flow into a political insubordination movement to the government that they consider infidels.